Are the immunomodulatory properties of Lactobacillus rhamnosus CRL1505 peptidoglycan common for all Lactobacilli during respiratory infection in malnourished mice? - Kolling, Yanina (PLoS One, 2018)
Previously, we reported that Lactobacillus rhamnosus CRL1505 peptidoglycan (PG05) improves the innate immune response in immunocompromised-malnourished mice after Streptococcus pneumoniae infection. This study extends those previous findings by demonstrating that the dietary recovery of malnourished mice with nasal administration of PG05 improves not only the innate immune response but the respiratory and systemic adaptive humoral response as well. PG05 enhanced the Th2 response, the recovery of B cells, and the concentration and opsonophagocytic activity of anti-pneumococcal antibodies. In addition, by performing comparative studies with the peptidoglycans from lactobacilli of the same species (L. rhamnosus CRL534) or with similar immunomodulatory properties (L. plantarum CRL1506), we demonstrated here that PG05 has unique immunomodulatory properties that cannot be extended to peptidoglycans from other probiotic strains. However, the knowledge of the molecular characteristics of PG05 is indispensable to understand immunomodulatory abilities of L. rhamnosus CRL1505.